Functional Outcome of Fracture Shaft of Femur Stabilised with Reamed Intramedullary Nail- A Prospective Study - Nishant Gaonkar, Ravindra Gunaki (International Journal of Advanced Science and Technology, 2020)
Introduction : Internal fixation of femoral shaft fractures has immensely developed since its advent in recent years. Though Intramedullary nailing (reamed) has gained popularity but still questions regarding the local and systemic effects of reaming still prevails.Aim:To evaluate the functional efficacy and outcome of fracture shaft of femur stabilised with reamed intramedullary nail.Material and methods:The present prospective observational study enrolled 60 patients who presented with femoral shaft fractures.The patients were classified according to the AO classification and we selected mainly type A or B fractures.Intraoperatively, we used 11-13 mm reamed nails, whatever was the desired size and  introduced to the canal.Post operatively, antibiotic Injectionsand pain killers were given according to the requirement.Follow up evaluation was done at 1 month, 3 months and 6 months following surgery.Results:Mean age of the study population was 29.82 years with males population of  51 (85%)and 9 (15%) females. Right side femoral shaft fractures (68.3%) were found to be more common.Most common cause of femoral fracture in our study was blunt trauma due to some road accident on vehicle accounting for 86.7% cases.The average length of hospital stay was l3.31 days (with a minimum of 6 days and a maximum of 28 days). The average time for radiological union observed in our study was 21 weeks. Full weight bearing was permitted between 6-18 weeks (with an average of 11.42 weeks). Total union rate as observed in our study came to be 55 cases (91.6%).Range of knee flexion was full in 51 (85%), 0-120 in 8 (13.3%), and 0-30 degrees in just 1 (1.6%) Complications faced by us were as follows: There were 2 cases (3.3%) ofnon-union, 1 case (1.6%) of delayed union and 1 case (1.6%) reported with malunion/ shortening. Various other complications observed in our study included infections and nail breakage. Over a follow up of 6 months period, progression was good with stabilization of the nailed fracture shaft.Conclusion:We conclude that functional outcome after fracture shaft of femur which is treated using reamed intramedullary nail turns to be good with good stabilization. We did not even face any serious pulmonary complications during our study. Therefore Intramedullary nailing seems to be an effective treatment procedure for femoral shaft fracturesKeywords: Femur shaft  fracture, intramedullary nailing, reamed nailing, functional outcome